Fra det prangende til det ydmyge: Kullede middelalderkirker i Danmark - Wienberg, Jes (Kuml, 2025)
From the ostentatious to the humble Towerless medieval churches in Denmark This article investigates a special category of medieval church – those without towers. The Danish concept of kullet, i.e. bald-headed, is discussed, an inventory of towerless churches is established for medieval Denmark and their architecture is analysed in relation to different ideals and studied from various social and economic perspectives. The churches in two parishes in Jutland, home of the iconic towerless church, are employed as case studies: Hover (fig. 1) and Sædding (fig. 2). Towerless churches are perceived as both historical sources and as an important aspect of our cultural heritage worthy of protection. Much research has been focused on church towers and the churches associated with them (fig. 3), together with the aristocracy and their manors. There is a need for an alternative perspective, highlighting the more ordinary churches – those without towers. Towerless churches are referred to in Danish as kullede, meaning bald-headed. Mention of a ‘bald’ church is seen for the first time in an atlas from 1768 in reference to Spørring church (fig. 4). These churches are perceived as a preserved architectural expression of the original Romanesque churches before Gothic transformation and other developments. They are also described in a romantic spirit, together with their surrounding landscape. Wooden churches of the 10th and 11th centuries do not appear to have had bell towers, while none of the masonry churches of the 11th century can be said with certainty to have been towerless. Research has, however, been undertaken into the major churches, and the first masonry churches may have been built on the initiative of kings, bishops or members of the aristocracy. From the 12th century, most churches in western Denmark were towerless from the outset, whereas a relatively greater number were given a tower in eastern Denmark. This was probably because peasant farms dominated in the west and aristocratic manors in the east. During the 15th century, up until the Reformation, many churches had a tower added, although some were later reduced or demolished, for example at Mårup (fig. 5), and a few towers were even added in later periods, making the towerless church a rarity. Different ideals existed for church architecture in the Middle Ages, as demonstrated by regulations against extravagance, including in architecture, applied by the Cistercians, Dominicans and Franciscans. A church might have a masonry tower added to it, but this was expensive and there were other and cheaper solutions, such as hanging the bells in a wooden belfry, a small bell cot, spire or ridge turret. An analysis is conducted here of the towerless churches in two parishes in Jutland: Hover and Sædding. The architecture of the churches is assessed in the light of the fees paid by the churches during the 14th century and the years 1524-26, an evaluation of the agriculture in the parish in 1682 and the existence of manors. Towerless churches are more frequent in places where the taxes in 1524-26 are relatively low, where the parishes are small and poor and where manors are absent (tab. 1). Towerless churches can be viewed partly as historical sources reflecting the social and economic topography of medieval Denmark, and partly as an important element of our cultural heritage reflecting the first phase of building masonry churches. All churches have, however, undergone changes and have had extensions such as porches added, even the iconic churches of Hover and Sædding. If one seeks a ‘genuine’ Romanesque church, as it might have appeared in the 12th Century, one must look to the church in the open-air museum Hjerl Hede in Jutland (fig. 6), where a church of this kind was reconstructed around 1950. An overview has been produced showing the existence of 339 towerless medieval churches in present-day Denmark, Southern Schleswig with Fehmarn, Scania, Halland and Blekinge (fig. 7; tab. 2), see catalogue in appendix to this article. The towerless churches are divided into two categories: A genuine and B illegitimate. The first never had a tower, while the second have a free-standing tower, have once had a tower, which was later reduced to the roof of the nave and a bell cot, a spire or a ridge turret has been added. The towerless churches are also divided into Romanesque and Gothic types, the latter being written in italics